Economic and financial benefits for wind turbines providing frequency response exploiting the kinetic energy or operating part‐loaded. Issue 20 (20th July 2020) - Trovato, Vincenzo; Conenna, Domenica; Dicorato, Maria; Forte, Giuseppe; Trovato, Michele
Abstract : This work assesses the financial viability of a wind farm where turbines are equipped to provide frequency services. Two control strategies are compared: the former enables the frequency response provision by operating the turbines part loaded, the latter employs the kinetic energy stored in the turbines' rotating masses. The analysis accounts for typical factors affecting the wind farm operation, the wake effect and the forecast errors on wind availability. A two‐stage optimisation model determines the day‐ahead and (close to) real‐time operation of the turbines, which profit from selling energy at the wholesale market (including subsidies), receiving availability payments for frequency services, while facing imbalance costs due to mismatches between forecasted and available wind. The two control strategies are applied to the Teesside Offshore Farm and the economic and financial performance are evaluated against a base case where the turbines do not provide frequency response service. Under current settings, the added value from frequency response capability is marginal. Changes to the market value of frequency services would favour the strategy based on part‐load operation of the turbines. The scheme based on the deployment of kinetic energy becomes profitable when the duration of time window for frequency response reduces.